2017
DOI: 10.5694/mja16.00650
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in patients with schizophrenia

Abstract: Patients with schizophrenia die on average 25 years earlier than the general population, and this gap appears to be increasing. Most of the excess mortality is due to premature cardiovascular deaths rather than suicide. Many psychotropic agents are orexigenic and can increase weight and promote dyslipidaemia. Traditional cardiac risk factors are undertreated among patients with schizophrenia, and they are less likely to receive cardiac revascularisation than those without a mental illness. Clozapine is an atyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 70 publications
(121 reference statements)
0
25
0
4
Order By: Relevance
“…We thank Skalicky for his interest in our article 1 . We agree that a rehabilitation approach to complement the model of care may be very helpful.…”
mentioning
confidence: 80%
“…We thank Skalicky for his interest in our article 1 . We agree that a rehabilitation approach to complement the model of care may be very helpful.…”
mentioning
confidence: 80%
“…Existing studies have shown that the life expectancy in patients with schizophrenia is 10 to 20 years shorter than that in people without schizophrenia [4]. One of the leading causes of premature death in patients with schizophrenia is cardiovascular disease [5][6][7]. Among the risk factors for cardiovascular disease, obesity is prominent and very common [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] As the results of premature cardiovascular disease, suicide, and cancer, the schizophrenia patients have a significantly shorter life span than their peers nearly 25 years. [3,4] Sudden cardiac deaths are more likely to occur in patients with schizophrenia. Psychiatrists therefore need actively concern on metabolic issues, such as obesity which could significantly increase the risk of cardiovascular diseases, in patients of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%